Fcγ receptor-mediated biological activities of human leukemic cell lines and their modulation by transforming growth factor-β1 and interleukin 6 - Morikawa, Minoru; Harada, Naoki; Nunomura, Yuka; Koike, Tsuneaki; Hashimoto, Seiji; Soma, Gen-ichiro; Yoshida, Takeshi (Cytokine (Philadelphia, Pa.), 1993)
Previously we reported that transforming growth factor-β1 (TGF-β1) remarkably enhanced the differentiation of human leukemic cell lines, HL-60 and THP-1, in the presence of 1α,25-dihydroxyvitamin D 3 (VD 3) and also that it induced Fc receptor for immunoglobulin G (FcγR), type IIIB, in the presence of retinoic acid (RA). The present study revealed that TGF-β1 enhanced the FcγRI- and FcγRII-mediated antibody-dependent cellular cytotoxicity (ADCC) of the cells differentiated in the presence of VD 3 and RA. However, production of active oxygen molecules was suppressed by TGF-β1. On the other hand, IL-6 stimulated production of active oxygen molecules and ADCC of the cells treated with VD 3 and tumor necrosis factor-α (TNF-α). Furthermore, the levels of cell surface FcγRI and FcγRII were not clearly correlated with the ADCC. The TGF-β1 VD 3-treated HL-60 cells were able to synthesize mRNAs for TGF-β1 and TNF-α, although TNF-α protein was not detectable. These results suggest that TGF-β1 has a bifunctional role, either stimulatory or inhibitory, in the modulation of macrophage activities through FcγRs and that IL-6 stimulates certain macrophage activities in mature cells.